Clinical findings of the second 1000 UK Gulf War Veterans who attended the Ministry of Defence's Medical Assessment Programme. Issue 2 (1st June 2001) - Lee, HA; Gabriel, R; Bale, A J; Bolton, P; Blatchley, NF
Abstract : Objective: To review the diagnoses made in the second 1000 veterans of the Gulf conflict 1990-91 seen in the Ministry of Defence's Gulf Veterans' Medical Assessment Programme and to determine the main conditions related to Gulf service. Design: Case series of 1000 consecutive Gulf veterans who presented to the programme between 25 February 1997 and 19 February 1998. Subjects: Gulf War veterans. Main outcome measures: Assessment of the patient's health status. Diagnosis of medical and psychiatric conditions using ICD-10. Results: 204 patients were unwell. 309 patients had organic disease, of whom 248 were well, 252 had psychiatric conditions which remained active in 173. The remaining 79, now well, had had psychiatric disorders following Gulf service. The principal psychiatric diagnosis was post traumatic stress disorder and the majority arose as a result of Gulf service. Conclusion: 796 (80%) veterans were well. There were 309 (31%) patients with organic disease. 252 (25%) veterans had psychiatric conditions of which 173 (69%) had an active diagnosed disorder and post traumatic stress disorder was the predominant condition. The pattern of disease is similar to that seen in NHS practice. We found, like others, no evidence to support a unique Gulf War syndrome. Post conflict illnesses have many common features.